Other-Regarding Virtues and Their Place in Virtue Argumentation Theory - Oliveira de Sousa, Felipe (Informal Logic, 2020)
In this paper, I argue that, despite the progress made in recent years, virtue argumentation theory still lacks a more systematic acknowledgment of other-regarding virtues. A fuller recognition of such virtues not only enriches the field of research of virtue argumentation theory in significant ways, but also allows for a richer and more intuitive view of the virtuous arguer. A fully virtuous arguer, it is argued, should care to develop both self-regarding and other-regarding virtues. He should be concerned both with his own development as an arguer and with helping other arguers in that regard.